x/3 + 2y/7 = -3/7 ———> 7x + 6y = -9 {multiplied top equation by 21}

y/4 + 2 = x/4 —-——-> y + 8 = x {multiplied bottom equation by 4}

7x + 6y = -9

7(y + 8) + 6y = -9 {substituted (y + 8), in for x, into top equation}

7y + 56 + 6y = -9 {used distributive property}

13y + 56 = -9 {combined like terms}

13y = -65 {subtracted 56 from each side}

y = -5 {divided each side by 13}

x = y + 8 {new 2nd equation from above}

x = -5 + 8 {substituted -5, in for y, into new 2nd equation, above}

x = 3 {added}

**x = 3 and y = -5 **
*- Algebra House*
**
**